The Role of Total Antioxidant Status in Cerebral Vasoreactivity of Chronic Obstructive Pulmonary Disease Patients - Marina Hlavati; Svetlana Tomić; Krunoslav Buljan; Silva Butković-Soldo (Southeastern European Medical Journal, 2020)
Introduction: Chronic obstructive pulmonary disease (COPD) is associated with an oxidant-antioxidant imbalance. COPD patients have impaired cerebral vasoreactivity (CVR). Impaired CVR could be correlated with total antioxidant status (TAS) in plasma.